Juridical Analysis Of The Effectiveness Of The Role Of The Port Authority and Port Authority Office (KSOP) In The Supervision Of Port Security and Safety In Indonesia: Batam Special KSOAP Office Research Study - Yuzirwan Nasution; Erniyanti Erniyanti; Ramlan Ramlan; Soerya Respationo (International Journal of Law, Crime and Justice, 2024)
The importance of the role of KSOP in ensuring the security and safety of ports in Indonesia, especially in Batam, which is one of the main ports in Indonesia. Batam Port has dense activities and has the potential to pose various security and safety risks. Therefore, the effectiveness of supervision by KSOP is crucial to prevent incidents that can harm many parties. The purpose of this study is to analyze the effectiveness of the role of KSOP in the supervision of port security and safety in the Batam Special KSOP area and identify the obstacles faced and efforts that can be made to overcome them. The research methods used are normative juridical and empirical juridical approaches with qualitative analysis. Data was obtained through the study of relevant laws and regulations, as well as interviews with related parties at KSOP Batam. The results of the study show that although KSOP Batam has tried to carry out supervision well, there are several obstacles that reduce its effectiveness. These obstacles include limited human resources and facilities, lack of coordination between agencies, weaknesses in law enforcement, and low awareness and compliance with safety regulations. In addition, challenges in technology and infrastructure also affect the effectiveness of surveillance. Based on these findings, this study provides several suggestions to increase the effectiveness of the role of Batam KSOP. First, increasing the number and quality of human resources through periodic training and certification. Second, strengthen coordination between related agencies through the establishment of an integrated command center. Third, improve the supervision and law enforcement process by implementing stricter and more transparent standards. Fourth, increasing awareness and compliance with safety regulations through continuous education campaigns. Finally, optimizing the use of modern technology and infrastructure to support more efficient and effective surveillance. With the implementation of these suggestions, it is hoped that KSOP Batam can significantly improve the safety and security of the port.